The practice of internet hospital for pediatric patients: a real-world study - Yin, Wen; Li, Zhuo; Gao, Chenzhong; Xu, Jin; Wang, Qian; Li, Wenjing (Frontiers in Pediatrics, 2025)
ObjectiveThe study analyzes real-world operational data of our pediatric internet hospital to improve operational efficiency, enhance user experience, and provide a reference for other hospitals launching similar platforms.MethodsWe analyzed the operational data of our pediatric internet hospital from June 1, 2020, to May 31, 2025, examining patient demographics, service utilization, diagnoses, and satisfaction metrics. We also assessed the platform's key modules-medical assistant services, online treatment, and chronic disease management.ResultsOver five years, the internet hospital registered 2,096,293 new users. A total of 259,034 patients used online follow-up services, with 175,654 prescriptions issued, while 266,321 patients utilized online consultation services. The majority (76.27%) of follow-up patients were under six years old, and services expanded to 31 provinces by 2025. Patient satisfaction was high, with an average score exceeding 9 out of 10. However, limitations in online physical examinations and diagnostic accuracy, along with policy-related restrictions, pose challenges to further expansion.ConclusionsInternet hospitals offer a valuable supplement to offline care, enhancing accessibility, particularly for children in remote areas. Despite certain operational limitations, internet hospitals have the potential to transform healthcare delivery in China. Further efforts should focus on expanding specialty services and addressing policy barriers to maximize their impact.